NEEDS ANALYSIS IN DEVELOPING ENGLISH CURRICULUM FOR EARLY CHILDHOOD AND ELEMENTARY SCHOOL STUDENTS: A CASE STUDY - Isnaniah Isnaniah; Nor Millah Hayati (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
The awareness of English language mastery leads to the effort of learning the language as early as possible. Since English is used as a foreign language in Indonesia, therefore English have to be introduced to the early childhood and elementary children institutions. When a foreign language is introduced to young learners, it requires special knowledge about how children acquire and learn language, so a proper learning method can be formulated as well. This research aims to conduct the needs analysis in developing English curriculum for early childhood and elementary school children. This research employed a case study research. It was carried out through surveys with relevant subject and related stakeholder at LKP SQUARE Education Center English Program Balai Pengembangan Pendidikan Anak Usia Dini dan pendidikan Masyarakat (BP-PAUD dan Dikmas) Kalimantan Selatan. The object of the research is the subject's response including the tendency of the teachers for applying the curriculum in their teaching activities, the students’ performance, and the students’ character. The data were collected through interview, questionnaire, and observation. The data were analysed descriptively. The finding showed that the young learners need to master English skill actively and confidently.Keywords- Needs Analysis, Curriculum Development, English for Young Learners